2020
DOI: 10.3390/antib9030032
|View full text |Cite
|
Sign up to set email alerts
|

Improving Receptor-Mediated Intracellular Access and Accumulation of Antibody Therapeutics—The Tale of HER2

Abstract: Therapeutic anti-HER2 antibodies and antibody–drug conjugates (ADCs) have undoubtedly benefitted patients. Nonetheless, patients ultimately relapse—some sooner than others. Currently approved anti-HER2 drugs are expensive and their cost-effectiveness is debated. There is increased awareness that internalization and lysosomal processing including subsequent payload intracellular accumulation and retention for ADCs are critical therapeutic attributes. Although HER2 preferential overexpression on the surface of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 133 publications
1
24
0
Order By: Relevance
“… 1 However, many novel anti-cancer biopharmaceuticals are perceived as providing insufficient benefits, and because they are expensive, their cost-effectiveness has been questioned. 2 , 3 Two major challenges limiting the full effectiveness of biopharmaceuticals are (1) the inability of large biological molecules to cross the plasma membrane while retaining target cell specificity, and (2) the need to improve the intracellular accumulation of biopharmaceuticals transporting payloads to sufficient levels to evoke an effective cellular response for the given therapeutic application. These barriers must be improved for next-generation biopharmaceuticals, yet insights and accompanying enhancing technologies are yet to be fully realized.…”
Section: Introductionmentioning
confidence: 99%
“… 1 However, many novel anti-cancer biopharmaceuticals are perceived as providing insufficient benefits, and because they are expensive, their cost-effectiveness has been questioned. 2 , 3 Two major challenges limiting the full effectiveness of biopharmaceuticals are (1) the inability of large biological molecules to cross the plasma membrane while retaining target cell specificity, and (2) the need to improve the intracellular accumulation of biopharmaceuticals transporting payloads to sufficient levels to evoke an effective cellular response for the given therapeutic application. These barriers must be improved for next-generation biopharmaceuticals, yet insights and accompanying enhancing technologies are yet to be fully realized.…”
Section: Introductionmentioning
confidence: 99%
“…The accelerated HER2 internalization in the presence of the polyclonal anti-HER2 antibody may be due to multi-epitope interactions of the antibodies with the receptor, thus crosslinking HER2 on the cell surface, leading to subsequent efficient endocytosis. Several studies have showed that a combination of antibodies with non-overlapping epitopes can lead to accelerated internalization [35]. For example, the combination of anti-HER2 antibodies trastuzumab (domain IV) and L26 (domain II) resulted in accelerated internalization of the HER2 receptor, tested in SK-BR-3 cells and transfected HEK-293T cells, respectively [36].…”
Section: Introductionmentioning
confidence: 99%
“…Antibody-drug conjugates (ADCs) are the most mature offshoot of unmodified mAb therapeutics [ 54 ]. ADCs are mAbs conjugated to a small molecule chemotherapeutic via a chemical crosslinker.…”
Section: Antibody-drug Conjugatesmentioning
confidence: 99%
“…Lysosomal proteases digest the antibody backbone or cleave the chemical crosslinker and liberate functional chemotherapeutic metabolites. The metabolites are able to permeate the lysosomal membrane and diffuse and bind their target and inhibit their function [ 54 ]. We highlight two recent clinically successful ADCs for bladder cancer.…”
Section: Antibody-drug Conjugatesmentioning
confidence: 99%
See 1 more Smart Citation